2016
DOI: 10.1371/journal.pone.0168171
|View full text |Cite
|
Sign up to set email alerts
|

miR-151-3p Targets TWIST1 to Repress Migration of Human Breast Cancer Cells

Abstract: TWIST1 is a highly conserved basic helix-loop-helix transcription factor that contributes to cancer metastasis by promoting an epithelial-mesenchymal transition and repressing E-cadherin gene expression in breast cancer. In this study, we explored the potential role of miR-151 in TWIST1 expression and cancer properties in human breast cancer cells. We found that the human TWIST1 3’UTR contains a potential binging site for miR-151-3p at the putative target sequence 5’-CAGUCUAG-3’. Using a TWIST1-3’UTR luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…The evidence about miR-151-3p is even scarcer. Several studies have observed a relationship with cancer 25,26 . Its association with atherosclerosis has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence about miR-151-3p is even scarcer. Several studies have observed a relationship with cancer 25,26 . Its association with atherosclerosis has not been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences showed that Twist1 decreases the expression of E-cadhrin [ 19 , 27 , 28 , 29 ], and the lack of E-cadherin can induce the expression of Twist1, so forms a positive feedback, keep cells in an interstitial state, so as to induce the EMT. Like in breast cancer cells [ 9 ], in SiHa and CaSki cervical cancer cell lines, we also found by luciferase assay that Twist1 promoter activity and expression were decreased by TQ.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BCL2L1 is regulated by miR-1266, miR-185, and miR-30c [60] in prostate cancer. TWIST1 is regulated by miR-151-3p in BC [61]. These miRNAs are involved in negative regulation of the apoptotic pathway and upregulation of invasion or migration respectively, but the role in BM is not clear yet.…”
Section: Extravasationmentioning
confidence: 99%